Glutaminase inhibition as potential cancer therapeutics: current status and future applications - Rajath Cyriac; Kwangho Lee (Taylor & Francis Group, 2024)
AbstractAlterations in normal metabolic processes are defining features of cancer. Glutamine, an abundant amino acid in the human blood, plays a critical role in regulating several biosynthetic and bioenergetic pathways that support tumour growth. Glutaminolysis is a metabolic pathway that converts glutamine into various metabolites involved in the tricarboxylic acid (TCA) cycle and generates antioxidants that are vital for tumour cell survival. As glutaminase catalyses the initial step of this metabolic pathway, it is of great significance in cancer metabolism and tumour progression. Inhibition of glutaminase and targeting of glutaminolysis have emerged as promising strategies for cancer therapy. This review explores the role of glutaminases in cancer metabolism and discusses various glutaminase inhibitors developed as potential therapies for tumour regression.